Maternal satisfaction on postnatal and neonatal care of babies treated for neonatal sepsis in secondary and tertiary care hospitals of a district in Sri Lanka - Chintha Jayasinghe; Chrisantha Abeysena (College of Community Physicians of Sri Lanka, 2020)
Introduction : Patient satisfaction is considered to be a vital component in the evaluation of the quality of care. Objectives: To describe the maternal satisfaction on care received by the neonates and mothers during their stay in the secondary and tertiary care hospitals in a district of Sri Lanka. Methods: This was a descriptive study conducted among 235 postpartum mothers of neonates who were treated for sepsis in the neonatal intensive care units. An interviewer-administered questionnaire was used to assess maternal satisfaction regarding the care received by the mothers (20 items) and neonates (20 items). The mothers were also requested to make suggestions for improvement. The questionnaire was administered on the day of discharge from the hospital. Overall satisfaction scores for maternal care and neonatal care were calculated separately and was considered satisfactory if it was more than 75% of the total score. Results: The overall mean satisfaction score for maternal care was 84.2 (range 49-100) and for neonatal care, it was 94.0 (range 52-98). Majority of the mothers were satisfied with the maternal care (n=208; 88.5%) and neonatal care (n=220; 93.6%). The majority were satisfied regarding the breastfeeding counselling (n=224; 93.3%), information on the treatment their neonates received (n=227; 94.6%) and investigations of the neonates (n=196; 81.7%). A higher percentage also recommended the obstetric unit to others as a favourable place (n=224; 93.3%) and preferred to return to the same unit for neonatal care for any future episode of illness (n=227; 94.6%). Conclusions: The overall maternal satisfaction regarding the neonatal and maternity care was high. There was a gap between the needs and provision of healthcare.